Euthanasia for people with psychiatric disorders or dementia in Belgium: analysis of officially reported cases - Dierickx, Sigrid (BMC Psychiatry, 2017)
BACKGROUND: Euthanasia for people who are not terminally ill, such as those suffering from psychiatric disorders or dementia, is legal in Belgium under strict conditions but remains a controversial practice. As yet, the prevalence of euthanasia for people with psychiatric disorders or dementia has not been studied and little is known about the characteristics of the practice. This study aims to report on the trends in prevalence and number of euthanasia cases with a psychiatric disorder or dementia diagnosis in Belgium and demographic, clinical and decision-making characteristics of these cases. METHODS: We analysed the anonymous databases of euthanasia cases reported to the Federal Control and Evaluation Committee Euthanasia from the implementation of the euthanasia law in Belgium in 2002 until the end of 2013. The databases we received provided the information on all euthanasia cases as registered by the Committee from the official registration forms. Only those with one or more psychiatric disorders or dementia and no physical disease were included in the analysis. RESULTS: We identified 179 reported euthanasia cases with a psychiatric disorder or dementia as the sole diagnosis. These consisted of mood disorders (N = 83), dementia (N = 62), other psychiatric disorders (N = 22) and mood disorders accompanied by another psychiatric disorder (N = 12). The proportion of euthanasia cases with a psychiatric disorder or dementia diagnosis was 0.5% of all cases reported in the period 2002–2007, increasing from 2008 onwards to 3.0% of all cases reported in 2013. The increase in the absolute number of cases is particularly evident in cases with a mood disorder diagnosis. The majority of cases concerned women (58.1% in dementia to 77.1% in mood disorders). All cases were judged to have met the legal requirements by the Committee. CONCLUSIONS: While euthanasia on the grounds of unbearable suffering caused by a psychiatric disorder or dementia remains a comparatively limited practice in Belgium, its prevalence has risen since 2008. If, as this study suggests, people with psychiatric conditions or dementia are increasingly seeking access to euthanasia, the development of practice guidelines is all the more desirable if physicians are to respond adequately to these highly delicate requests. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-017-1369-0) contains supplementary material, which is available to authorized users.